Effects of High-Fat Diet on Carcinogen-Induced Pancreatic Cancer and Intestinal Microbiota in C57BL/6 Wild-Type Mice. Issue 4 (April 2021) - Liu, Beibei; Wang, Furong; Chen, Lina; Xin, Yi; Liu, Likun; Wu, Dachang; Li, Weiling
Abstract : Objectives: High-fat diet has been considered a risk factor for the development of pancreatic cancer. It is also shown to significantly impact composition and dysbiosis of gut microbiota in both humans and animals. However, there is little information on the effect of high-fat diet on the development of pancreatic cancer or upon the gut microbiota of patients with pancreatic cancer in humans or animal models. Methods: In this study, the effect of high-fat diet on cancer pathology and the gut microbiota was investigated by a carcinogen-induced pancreatic cancer mouse model. Results: Compared with carcinogen alone, mice with high-fat diet and carcinogen showed more obvious pathological changes in pancreatic tissue; increased levels of proinflammatory cytokine tumor necrosis factor-α, interleukin-6, interleukin-10, and carbohydrate antigen 242; and increased expression of cancer-associated biomarkers mucin-4 and claudin-4 in pancreatic tissue. Moreover, there is a significant change in the gut microbiota between the carcinogen group and the carcinogen with high-fat diet group. We identified that Johnsonella ignava especially existed in the carcinogen with high-fat diet group, which may contribute to pancreatic cancer development. Conclusions: Our results revealed that high-fat diet changed the composition of the gut microbiota and was involved in carcinogen-induced pancreatic cancer progression.